Experiences of bullying and exclusion among autistic students in Ireland: Neuro-affirming recommendations for bullying prevention. - Lynam, Aoife (DCU Anti-Bullying Centre., 2025)
School bullying is a damaging social process that is characterised by an imbalance of power driven by societal and institutional norms. It is often repeated and manifests as unwanted interpersonal behaviour among students or school personnel that causes physical, social, and emotional harm to the targeted individuals or groups, and the wider school community (UNESCO Chair on Bullying and Cyberbullying, 2024). This can include less visible forms of bullying such as social exclusion. Autistic students are disproportionately affected by bullying1 in post-primary education, which is likely due to a more complex social context and increased peer scrutiny (Cappadocia et al., 2012; Sterzing et al., 2012). Autism is a lifelong developmental disability or difference which relates to how a person communicates and interacts with others, and how they experience the world around them (AsIAm, 2025). Research suggests that autistic students frequently experience bullying in forms such as social exclusion, emotional bullying, and verbal harassment (Park et al., 2020). Recent studies have reported that autistic students are over twice as likely to experience bullying as their neurotypical peers, and more likely to be bullied than students with other disabilities (Park et al., 2020; Badger et al., 2024). Autistic students in mainstream settings also experience higher rates of peer bullying than autistic students in special education settings (Zablotsky et al., 2014)
PUBLISHED
Keywords: Inclusive Society; Autistic Spectrum disorders